2013
DOI: 10.5194/cp-9-447-2013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-periodic climate dynamics: spectral analysis of long-term instrumental and proxy temperature records

Abstract: The longest six instrumental temperature records of monthly means reach back maximally to 1757 AD and were recorded in Europe. All six show a V-shape, with temperature drop in the 19th and rise in the 20th century. Proxy temperature time series of Antarctic ice cores show this same characteristic shape, indicating this pattern as a global phenomenon. We used the mean of the six instrumental records for analysis by discrete Fourier transform (DFT), wavelets, and the detrended fluctuation analysis (DFA). For com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Astronomically-based semi-empirical harmonic models to reconstruct and forecast climatic changes are being proposed by several authors (e.g. : Abdusamatov, 2013;Akasofu, 2013;Lüdecke et al, 2013;Salvador, 2013;Scafetta, 2010Scafetta, , 2012aScafetta, ,b,d, 2013aSolheim, 2013a).…”
Section: Astronomically-based Semi-empirical Harmonic Climate Modelsmentioning
confidence: 99%
“…Astronomically-based semi-empirical harmonic models to reconstruct and forecast climatic changes are being proposed by several authors (e.g. : Abdusamatov, 2013;Akasofu, 2013;Lüdecke et al, 2013;Salvador, 2013;Scafetta, 2010Scafetta, , 2012aScafetta, ,b,d, 2013aSolheim, 2013a).…”
Section: Astronomically-based Semi-empirical Harmonic Climate Modelsmentioning
confidence: 99%
“…Babich et al [15] have found periods of ~1000, ~500 to ~350, and ~200 years in paleoreconstruction of the last 2000 years, predicting a strongly pronounced cooling until AD 2500. In this context, we need to mention Schlesinger and Ramankutty [16], Gervais [17], De Vries [18], Suess [19], Steinhilber et al [20,21], Breitenmoser et al [22], Cliver et al [23], Raspopov et al [24], Novello et al [25], Wagner et al [26], Lüdecke et al [27,28], Friis-Christensen and Lassen [29], Van Geel et al [30], Braun et al [31], Lohmann and Schöne [32], Czymzik et al [33], Adolphi et al [34], Wirth et al [35], Lockwood [36], Fleitmann et al [37], Svensmark [38], Svensmark et al [6], Marsh and Svensmark [39], Enghoff [40], Gray et al [41], Haigh [42,43], Ineson et al [44], Seidenglanz et al [45], Kodera [46], Meehl et al [47], and Leal-Silva and Herrera [48]. Lüning [49] provides an extensive compilation of pertinent references.…”
Section: Introduction / Overviewmentioning
confidence: 99%
“…The series is mean corrected for the signal analysis. This paleoproxy record is used to assess decadal to century time scale cycles [ Battisti , ; Li et al ., ; Lüdecke et al ., ] ( ftp://ftp.ncdc.noaa.gov/pub/data/paleo/treering/reconstructions/enso-li2013.txt). Logistic map [ Feigenbaum , ]. The logistic map is used to provide the 2n2, 3n2, and 3n2+I period doubling subharmonic universal features.…”
Section: Analysis Methods and Datamentioning
confidence: 99%
“…The series is mean corrected for the signal analysis. This paleoproxy record is used to assess decadal to century time scale cycles [Battisti, 1995;Li et al, 2013;L€ udecke et al, 2013] (ftp://ftp.ncdc.noaa.gov/pub/data/ paleo/treering/reconstructions/enso-li2013.txt). D. Logistic map [Feigenbaum, 1980].…”
Section: Datamentioning
confidence: 99%